A Remotely-Delivered CBT and Contingency Management Therapy for Substance Using People with HIV. - Moore, Brent A; Rosen, Marc I; Wang, Yan; Shen, Jie; Ablondi, Karen; Sullivan, Anna; Guerrero, Mario; Siqueiros, Lisa; Daar, Eric S; Liu, Hong Hu (AIDS and behavior, 2015)
Substance using HIV patients are at risk for non-adherence, and most prior interventions in this population have had only modest effects on adherence. Contingency management (CM) is a promising intervention. The Centralized Off-site Adherence Enhancement (CARE) program involved 12 telephone-delivered substance and adherence-targeted cognitive behavior therapy sessions coupled with CM for adherence to antiretroviral therapy (ART) and counseling participation. CM involved 6 weeks of escalating reinforcement for taking prescribed doses followed by 6 weeks of tapering variable rate reinforcement, and separate reinforcement for counseling ($806 possible). Participants' adherence was measured by devices which wirelessly provided real-time notification of device-opening. HIV infected patients on ART (N = 10) with recent stimulant or alcohol use completed 10.2 of 12 possible telephone sessions, spent 42.8 min/call, and rated the counseling 6.2 on a 1-7 scale. Medication adherence improved from 81 to 93 % (p = 0.04). CARE appears to be acceptable and engaging.
Keywords: Adult; Anti-Retroviral Agents; California; Cognitive Therapy; Directive Counseling; Feasibility Studies; Female; HIV Infections; Humans; Male; Medication Adherence; Motivation; Patient Acceptance of Health Care; Program Evaluation; Substance Abuse, Intravenous; Substance-Related Disorders; Telephone; Treatment Outcome; Young Adult